Análise e simulação de controle volumétrico e dinâmico em sistemas de perfuração de poço - Silva, Juliana Gomes da (Brasil, 2021)
Controlling a gas inflow (kick) and preventing an eruption (blowout) while drilling an oil well is not an easy task, so a fast, viable and efficient control plan is needed. Strict well control in the production of oil and gas can prevent these undesirable inflows and several economic and environmental problems. Therefore, the objective of this work is to make an analysis of the pressure behavior, during the circulation of a kick, through the development of a well control simulator using the dynamic volumetric method. Considering aspects such as minimum inflow volume, deepwater offshore situations for different water depth scenarios and the influence of control fluid parameters on pressure behavior. The simulator will respond to well control in drilling operations with the introduction of new resources that help professionals in the area to make decisions during the occurrence of an undesirable inflow. To develop the simulator, the methodology applied in the dynamic volumetric control will be based on the mathematical modeling of NUNES (2002). Kick in deep wells, as it is an area of difficult access, technological advances become limited. Bearing in mind that a simulator is important in optimizing well control in drilling operations, which will allow the analysis of the behavior of pressures on the surface and inside the well, being able to assist other well projects during drilling. The kicks simulator for deepwater offshore environment will be elaborated through a computational code in the JAVA program, which aims to monitor the behavior of the pressures in the annular and the choke line from the reading of the well data (diameters, depth and volumetric capacity ), fluid (density and rheology), gas inflow and geopressures.